FUNDAMENTAL INVESTIGATION OF OIL/WATER FLOW IN THE DOWNHOLE - ABDUL JAMIL, IYLIA ELENA (2016)
Oil/water mixture production in the wells is a common phenomenon. It is of high interest to the oil industry to process the oil/water separation in the downhole, by hydrocyclone technology. Oil and water separation methods have focused on the separation process and the hydro fluid behavior within the separator body while there is a lack of studies and simulations on the wellbore flow behavior before and after the separation. Accordingly, this work is directed to investigate the mixture flow structure in the production and in the water dumping zones.